Spectrum™ Method - Dus, Clare; Stapleton, Lee; Trail, Amy; Krogmann, Annlyse Retiveau; Civille, Gail Vance (Descriptive Analysis in Sensory Evaluation, 2018)
The flexibility in the Spectrum TM Method can be traced from its historical development from descriptive analysis’ first beginnings with the Flavor Profile and Texture Profile methodologies. The changes to improve descriptive analysis techniques from its historical roots include the Spectrum™ method expanding qualitative and intensity references and scale expansion to 151 points of differentiation. The Spectrum™ method was also broadened to not cover just food and food ingredient products but also personal care and paper products. The process of setting up a Spectrum™ trained panel is explained in overview including all aspects of consideration such as selecting the panelists, qualities of a good panel leader, training structure and processes, and finally how to validate and maintain a functioning Spectrum™ panel. The concluding sections demonstrate how the Spectrum™ method is versatile and can be adapted across different modalities and merged with different sensory and consumer research methods to support research hypotheses.